Go beyond tokens: Number and type both matter. Issue 4 (25th May 2021) - Wang, Yu; Luo, Xiaoyi; Wang, Tienan; Hu, Die
Abstract: Drawing upon token theory and critical mass theory, this study examines whether all female directors are equally considered as tokens. We argue that inside female directors are less likely than outside female directors to be considered as tokens because they are more powerful and influential. Using a 10‐year sample of Chinese publicly listed firms on the Shanghai or Shenzhen Stock Exchanges from 2008 to 2017, we find that even one inside female director can make a significant contribution to corporate social responsibility (CSR), while outside female directors do not have a positive effect on CSR until their number reaches the critical mass (i.e., three). The results suggest that the predictions of token theory and critical mass theory vary across female director types. These findings contribute to the current literature by integrating female director typology with their numerical representation to explain their token status.